Frequency and Causes of Conversion of Laparoscopic Cholecystectomy into Open Cholecystectomy (Medical Forum Monthly, 2024)
Objective: To determine the frequency and causes of conversion of laparoscopic cholecystectomy into open cholecystectomy.Study Design: Cross-sectional (descriptive) studyPlace and Duration of Study: This study was carried out at Surgical Unit of Postgraduate Medical Institute, Lady Reading Hospital, Peshawar for 14 months, from 1-11-2010 to 31-12-2011.Patients and Methods: A total of 126 patients of symptomatic gallstones disease fulfilling the inclusion criteria were subjected to laparoscopic cholecystectomy and were followed through out the procedure to see for any conversion and its cause.Results: The mean age of patients was 40.65±10.35 with range of 20-65 years. The total no of cases converted to open cholecystectomy were 11 out of 126. Thus frequency of conversion was 11 equal to 8.7%, with commonest cause being adhesions 9 out of 11 converted cases followed by hemorrhage 2 out of 11 conversions. Moreover conversion was more in male patients. 20.8% as compared to 5.9% in females.Conclusion: Laparoscopic cholecystectomy is the gold standard treatment modality in the management of symptomatic gallstones disease. Its one disadvantage is the conversion into open procedure. But conversion should not be considered as complication of the procedure rather it is mature decision by the surgeons to avoid unnecessary lengthening the duration of surgery once they encounter any difficulty or interoperative complication.